TRANSFORMATION OF H.P. LOVECRAFT’S COLOUR OUT OF SPACE SHORT STORY INTO MOVIE - Wira Indah Ayu; Husni Thamrin; Kunkun K. Harnady; Iwan Dudy Gunawan (Institut Pendidikan Indonesia Garut, 2022)
The Research Entitled